Pressure generated from head garment with padding insert used for hypertrophic scar treatment - Aiman, A.F.; Salleh, Mohamed Najib; Ismail, K.A. (Trans Tech Publications, Switzerland, 2015)
Pressure garment is a standard non-surgical treatment for hypertrophic scar caused by burn injury. However, the main problem identified was the non-uniform pressure distribution due to the complexity of the contour at the facial area. Therefore, padding was developed to produce more efficient pressure distribution. This study used 3D scanning apparatus to obtain the cross sections of the facial area. The padding was developed using 3D modeling software which act as an insert to fill the gaps at the contact area of the garment and facial areas. The result shows that by inserting the padding underneath the garment, the pressure outputs indicate an acceptable pressure range with the suitable reduction factor for the head garment fabrication.